An Encompassing, Normative Philosophy of Design: The Theory of Responsive Cohesion - Fox, Warwick (Conatus - Journal of Philosophy, 2024)
Design is concerned with the ways in which we deliberately seek to arrange, organize, or structure things. From a philosophy of design perspective, the practice of design raises fundamental questions about the basic ways in which things can and should be organized. I advance a tripartite schema of the basic ways in which things (anything at all) can be organized and offer a triangular model of the “organization space” or “design space” they define. I refer to these three basic forms of organization as “responsive cohesion,” “fixed cohesion,” and “discohesion,” and offer three reasons why responsively cohesive forms of organization are more valuable than the other two; indeed, the other two forms of organization are typically disvaluable. Beyond focusing on the value of individual instances of responsive cohesion, I further consider the fact that every responsively cohesive item exists within a wider context(s), which may itself tend more towards fixed cohesion, responsive cohesion, or discohesion. This raises a number of further issues; for example, what should we do if a responsively cohesive item clashes with – is discohesive with – its responsively cohesive context? I advance a normative theory of contexts to sort out these kinds of issues. In the context of this discussion, I briefly consider a range of other ideas that bear a family resemblance to the idea of responsive cohesion and indicate, equally briefly, why the theory of responsive cohesion approach is superior to these other approaches. I conclude with some guidance on how we can implement the ideas advanced here (“we” because we all design things in our own way) and then, more specifically, on the implications of these ideas for the professional designer-client relationship.